Analisa Kinerja Algoritma TCP Congestion Control Cubic, Reno, Vegas Dan Westwood+ - Aria Tanzila Harfad; Sabriansyah Rizqika Akbar; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Transmission control protocol (TCP) is a protocol at the transport layer that provides a reliable data transfer mechanism, so that the data stream reads TCP receiver is not corrupted, without duplication, and sequentially. To provide reliable data transfer, TCP provides error checking and flow control services. When the TCP sender sends data faster than the TCP receiver can handle, congestion will occur. TCP implements a congestion control mechanism for network traffic control so no congestion occurs. This study compares the performance of four variants of TCP congestion control, namely TCP Cubic, Reno, Vegas and Westwood +. The test is to analyze cwnd, ssthresh and throughput of four types of TCP Congestion Control algorithm. The author uses two devices as a sender and receiver. Both are connected with an ethernet cable that has a connection with 100Mbit/s bandwidth. TCP data is collected on the sender side using TCP Probe and the result is shown as a graph with Gnuplot. The results of this study indicate that TCP Westwood + is the best among the three other TCPs in all Service Center agreement (SLA) service provider environments with Bandwidth Estimation mechanisms they use.